2020
DOI: 10.1021/acs.jpclett.0c01537
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Temperature Dependence of Exciton Spectral Diffusion in Tetracene Thin Film

Abstract: In this work, an ultrafast spectral diffusion of the lowest exciton in a tetracene ultrathin film is studied by two-dimensional electronic spectroscopy. From the analysis of the nodal line slope, the frequency-fluctuation correlation function (FFCF) of the exciton band is extracted. The FFCF contains two components with decay times of 400 and 80 fs; while the former can be understood by a linear exciton–phonon coupling model, the latter shows an order of magnitude increase in its amplitude from 96 to 186 K tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Notably, a significant acceleration of the decay of the CLS with increasing the temperature is observed, which cannot be accounted for by the linear-coupling model with a harmonic bath. This is a qualitatively similar feature as we have reported on the tetracene thin film, indicating the ubiquity of the phenomena. We propose an anharmonic coupling model as the underlying mechanism, in which the energy gap fluctuation by a high-frequency intramolecular vibration is enhanced by coupling with a low-frequency phonon mode.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, a significant acceleration of the decay of the CLS with increasing the temperature is observed, which cannot be accounted for by the linear-coupling model with a harmonic bath. This is a qualitatively similar feature as we have reported on the tetracene thin film, indicating the ubiquity of the phenomena. We propose an anharmonic coupling model as the underlying mechanism, in which the energy gap fluctuation by a high-frequency intramolecular vibration is enhanced by coupling with a low-frequency phonon mode.…”
Section: Introductionsupporting
confidence: 89%
“…Recently, the authors have reported on temperature dependence of spectral diffusion dynamics of excitons in a tetracene thin film . By analyzing the 2DES signals, the FFCF of the lowest exciton transition was successfully extracted.…”
Section: Introductionmentioning
confidence: 99%
“…2D IR is the most common ultrafast multidimensional spectroscopic technique. However, with the development of ultrafast two-dimensional terahertz, Raman, optical, and sum-frequency generation spectroscopies, 2D IR is now just one of several ultrafast two-dimensional methods, and analysis tools originally developed for 2D IR, including center line slope, nodal line slope, , and diagonal slices, , have found uses in other ultrafast multidimensional techniques. PSAs provide a straightforward method to simplify two-dimensional spectroscopic data and may find emergent applications outside of 2D IR/FTIR comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the usual assumption that the two-particle bright state is dominatedby the state j ⃗ k b i ⊗ j2 ⃗ k b i, the direct product of the one-particle bright state and the one-particle state of double quasimomentum [52,53], with the bright state wave vector ⃗ k b ¼ k b ð− sin ϕ μ ; cos ϕ μ Þ, i.e., perpendicular to the transition dipole moment. Ignoring two-exciton interactions, the splitting between the two peaks is…”
Section: Applying the Bloch Theorem The Energy Dispersion Relation Readsmentioning
confidence: 99%